Kelas Ibu Hamil terhadap Kecemasan Ibu Primigravida - Desi Ratnasari; Rifa Yanti; Fajar Sari Tanberika; Rizka Mardiya (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of prenatal classes on anxiety levels among primigravida mothers in the Pangkalan Kasai Community Health Center (UPT Puskesmas) working area, Indragiri Hulu Regency. The research method used was a pre-experimental study with a one-group pretest-posttest design. The results showed a decrease in anxiety levels among primigravida mothers after attending prenatal classes, with a p-value of 0.000 (<0.05), indicating a significant effect of prenatal classes on anxiety among primigravida mothers. In conclusion, prenatal classes significantly reduced anxiety levels among primigravida mothers. Therefore, the implementation of prenatal classes needs to be continuously improved, regularly, and structured, as a promotive and preventive effort to improve the mental preparedness of pregnant women for pregnancy and childbirth. Keywords: Primigravida Mothers, Anxiety, Prenatal Classes